Extracytoplasmic stress responses induced by a model secretin : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, Manawatū, New Zealand - Spagnuolo, Julian (Massey University, 2015)
Pathogenic bacteria export large proteins and protein complexes, including virulence factors, using dedicated transenvelope multiprotein machinery, collectively called secretion systems. Four of these protein export machines found in Gram-negative bacteria, type 2/3 secretion systems, filamentous phage assembly-secretion system and the type 4 pilus assembly system contain large homologous gated channels, called secretins, in the outer membrane. Secretins are radially symmetrical homomultimers (luminal diameter 6-8 nm) interrupted by an internal septum or gate. Expression of these channels imposes a fitness cost to bacteria. While stress induced by model secretin pIV has been previously investigated using microarrays, this thesis is the first RNAseq characterisation of secretin stress responses. Furthermore, this is the first comparison of stress imposed by a closed-gate secretin (wildtype pIV), vs. an isogenic leaky-gate variant, the latter serving as a model of an open-gate substrate-secreting channel. The high sensitivity to changes in gene expression and low background noise of the RNA-seq approach have greatly expanded the known secretin stress responses to include the SoxS, CpxR and RcsB/RcsAB regulons, in addition to the known involvement of the Psp response. A synthetic lethality analysis of candidate genes in these pathways suggested that the leaky-gate secretins, besides rendering the Psp response essential for survival, also stimulate the SoxS and RcsB/RcsAB regulons for protection of the cells. Knowledge of the secretin stress expanded by this work helped identify potential targets for development of much-needed antibiotics against toxinsecreting Gram-negative bacteria.
Keywords: Gram-negative bacteria; Pathogenic bacteria; Bacterial cell walls; Secretins; Stress